2007
DOI: 10.1080/00207140601009157
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotizability, Eating Behaviors, Attitudes, and Concerns:A Literature Survey

Abstract: The literature suggests that aspects of hypnotizability may be involved in the etiology and maintenance of self-defeating eating. However, interpretation of the published research findings has been complicated by the use of instruments that appear to have measured different or, at best, only related facets of the underlying constructs. This article reports relationships between weight, shape, dietary concerns, hypnotizability, dissociative capacity, and fantasy proneness. Implications for a key role for hypnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…A recent systemic review of the use of acupuncture in cocaine dependence identified a total of seven RCTs involving a total of 1,433 subjects. hypnosis in BN is characterized by a small number of clinical studies, mostly case and anecdotal reports, and narrative reviews discussing methodological issues including the capacity of individuals to respond to hypnosis and different clinical approaches to the use of hypnosis (Anbar & Savedoff, 2005;Barabasz, 2007Barabasz, , 2012Hutchinson-Phillips, Gow, & Jamieson, 2007;Mantle, 2003;Torem, 1992;Túry et al, 2011;Walsh, 2008Walsh, , 2010. Outcome measures included cocaine use, measured either biochemically or by self-report, cocaine craving, severity of dependence, and treatment dropout.…”
Section: Acupuncture and Substance Use Disordersmentioning
confidence: 99%
“…A recent systemic review of the use of acupuncture in cocaine dependence identified a total of seven RCTs involving a total of 1,433 subjects. hypnosis in BN is characterized by a small number of clinical studies, mostly case and anecdotal reports, and narrative reviews discussing methodological issues including the capacity of individuals to respond to hypnosis and different clinical approaches to the use of hypnosis (Anbar & Savedoff, 2005;Barabasz, 2007Barabasz, , 2012Hutchinson-Phillips, Gow, & Jamieson, 2007;Mantle, 2003;Torem, 1992;Túry et al, 2011;Walsh, 2008Walsh, , 2010. Outcome measures included cocaine use, measured either biochemically or by self-report, cocaine craving, severity of dependence, and treatment dropout.…”
Section: Acupuncture and Substance Use Disordersmentioning
confidence: 99%
“…Sapp et al (2007), there appears to be some evidence accrued attesting to a degree of correlation between hypnotisability and weight loss (Allison, 2001;Barabasz, 2007), as well as hypnotisability having a significant relationship with a number of behavioural and cognitive eatingassociated characteristics such as weight, shape and dissociation (Hutchinson-Phillips et al, 2007), and playing a role in body self-image malleability (Frasquilho et al, 1998). …”
Section: A Brief History Of Clinical Hypnosis For Obesitymentioning
confidence: 99%
“…This same conclusion was reached by Byrom (2009) in a study comparing CBT alone with CBT plus hypnosis, whilst Prag (2007) in her single case study found this combination useful also for improving self-and body image, even in the absence of significant weight loss. Holt, Warren & Wallace (2006), Barabasz (2007) and Kothian (2009) all make the case for the usefulness of hypnosis for weight reduction although, the paucity of recent published trials means that their opinions are still based on those trials undertaken over 15 years previously.Even the most recent reviews by Hartman ( , there appears to be some evidence accrued attesting to a degree of correlation between hypnotisability and weight loss (Allison, 2001;Barabasz, 2007), as well as hypnotisability 6 having a significant relationship with a number of behavioural and cognitive eatingassociated characteristics such as weight, shape and dissociation (Hutchinson-Phillips et al, 2007), and playing a role in body self-image malleability (Frasquilho et al, 1998 …”
mentioning
confidence: 99%